Challenges in Mechanics of Time Dependent Materials, Volume 2 - Antoun, Bonnie; Arzoumanidis, Alex.; Qi, H. Jerry; Silberstein, Meredith; Amirkhizi, Alireza; Furmanski, Jevan; Lu, Hongbing; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Challenges in Mechanics of Time-Dependent Materials, Volume 2 of the Proceedings of the 2016 SEM Annual Conference& Exposition on Experimental and Applied Mechanics, the second volume of ten from the Conference, brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Experimental Mechanics, including papers in the following general technical research areas: Extreme Environments & Environmental Effects Structure-Function of Performance of PE Effects of Inhomogeneities & Interfaces Characterization Across Scales Mechanics of Energy & Energetic Materials Metallic Materials Viscoelasticity & Viscoplasticity.
Keywords: Civil Engineering; Characterization and Evaluation of Materials; Structural Materials